Is There a Skills Crisis? Trends in Job Skill Requirements, Technology, and Wage Inequality in the United States - Michael J. Handel (Levy Economics Institute of Bard College, 2000)
Many economists and other social scientists and policy makers believe that the growth in inequality in the last two decades reflects mostly an imbalance between the demand for and the supply of employee skills driven by technological change, particularly the spread of computers. However, the empirical basis for this belief is not strong. The growth in inequality was concentrated in the recession years of the early 1980s and any imbalance between the supply of and demand for workers with technological skills likely did not occur until later. The growth of the supply of more-educated workers decelerated during the 1980s, but any impact of that likely would not have been felt until the late 1980s and 1990s. However, inequality actually stabilized during this latter period. On the demand side, trends in occupational composition do not suggest that upgrading was particularly rapid in the 1980s and 1990s compared to the 1970s. Computers do not seem to have greatly affected employment in a number of narrow occupations that are likely to be sensitive to technological change (e.g., computer programmers, bank tellers). Computer use itself does seem to be associated with more education, even controlling for occupation, but the causal status of this relationship is uncertain and even the magnitude of the observed association does not seem large enough to have seriously compromised the ability of supply to meet the implied growth in demand. By contrast, the recession of the early 1980s coincides with a dramatic decline of traditionally better paid blue collar workers, particularly in manufacturing. This suggests a need for a closer look at other possible causes of inequality growth, such as macroeconomic forces and the decline of institutional protections for workers.
Keywords: 330